Four-flanged, intrascleral fixation of foldable intraocular lens using straight-needled 7-0 polypropylene suture – A surgical technique - Vellam R Vivekanandan; Sivagami Nachiappan; Annamalai Odayappan; Naveen N Gangapatnam; Merlin Benzy; Rengaraj Venkatesh (Indian Journal of Ophthalmology, 2025)
The occurrence of intraocular lens (IOL) implantation failure in phacoemulsification is relatively uncommon. However, because cataract surgery is the most prevalent surgical procedure worldwide, the aggregate instances of post-surgical aphakic status are significant. Though several alternatives, including anterior chamber IOL, iris-fixated IOL, and scleral-fixated IOL (SFIOL), exist for secondary IOL implantation, recent trends favor SFIOL implantation. In the realm of SFIOLs, all sutureless variants necessitate the exteriorization of the haptic through the sclera, implying a larger sclerotomy. Sutured SFIOL requires special lenses and typically involve rigid ones, which necessitate a larger incision. We describe a technique that involves utilizing a straight-needled 7-0 polypropylene suture for the 4-flanged intrascleral fixation of any foldable IOL that can be manually loaded onto a cartridge. This method combines the advantages of a reduced incision size and a smaller sclerotomy, addressing concerns associated with both sutureless and rigid SFIOL implantation.